2008
DOI: 10.1016/j.cct.2007.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials attitudes and practices of Latino physicians

Abstract: Background-Ethnic differences in physicians' attitudes and behaviors related to clinical trials might partially account for disparities in clinical trial participation among Latino patients. Literature regarding Latino physicians' involvement in clinical trials, in comparison to White physicians, could not be found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 26 publications
1
27
1
Order By: Relevance
“…242 In fact, care providers, especially physicians, tend to act as gatekeepers and provide the majority of patient education and coordination regarding clinical trials. 243,244 Evaluations of medical researchers' opinions about low minority recruitment have identified a perception of lower interest in clinical trials among minority patients (due to mistrust of researchers and lack of awareness/information and resources), a lack of investigator confidence in explaining clinical trials in culturally appropriate terms as probable barriers, and the paucity of collegial relationships between university-based physicians and many community physicians caring for minority patients. 245 Other data indicate that a large proportion of study principal investigators do not set a priori recruitment goals for racial-ethnic minorities, even though the number of minority participants needed for hypothesis testing may differ substantially from the numbers needed for more exploratory analyses aimed at generating new hypotheses.…”
Section: Structural Factors (Health and Research Systems And Economicmentioning
confidence: 99%
See 1 more Smart Citation
“…242 In fact, care providers, especially physicians, tend to act as gatekeepers and provide the majority of patient education and coordination regarding clinical trials. 243,244 Evaluations of medical researchers' opinions about low minority recruitment have identified a perception of lower interest in clinical trials among minority patients (due to mistrust of researchers and lack of awareness/information and resources), a lack of investigator confidence in explaining clinical trials in culturally appropriate terms as probable barriers, and the paucity of collegial relationships between university-based physicians and many community physicians caring for minority patients. 245 Other data indicate that a large proportion of study principal investigators do not set a priori recruitment goals for racial-ethnic minorities, even though the number of minority participants needed for hypothesis testing may differ substantially from the numbers needed for more exploratory analyses aimed at generating new hypotheses.…”
Section: Structural Factors (Health and Research Systems And Economicmentioning
confidence: 99%
“…Hispanic/ Latino physicians tend to be significantly less likely than their non-Hispanic white counterparts to find clinical trials to be of scientific value, which probably determines whether they recommend them to their patients. 243 There is relatively limited information in the literature on the enrollment and retention of minority women in clinical …”
Section: Structural Factors (Health and Research Systems And Economicmentioning
confidence: 99%
“…Physicians act as gatekeepers and provide a majority of patient education regarding clinical trials; therefore, they influence recruitment and patient decision-making. Research has shown that participation and recruitment barriers include physicians' lack of clinical trial awareness, attitudes, level of comfort explaining the trial, fear of losing patients, mistrust of medical institutions and researchers, lack of time and structural support, limited resources for data management, complexity of the study protocol and level of burden, feelings about the patient's age and comorbid conditions, and lack of adequate compensation for involvement [1,2,[8][9][10][11][12][13][14][15][16][17][18][19][20]. Physicians may also feel that referring patients to trials might negatively affect and threaten their relationship with patients, manifesting in patients either blaming the physician for any negative consequences of study participation or threatening the physician's income as patients seek increasing care via trial physicians [17,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Physicians may not offer or even discuss clinical trials as a treatment option with minority patients specifically, because they may perceive that these patients face unique barriers: mistrust of researchers and the medical system; lack of interest, awareness/information and resources; insufficient health literacy to understand the trial; and limited protocol compliance [2,8,9,11,12,14,17,20,24]. Other known barriers to the referral of minorities include providers' inadequate language proficiency [20,25,26] and inadequate means of presenting information to patients [2,9,20,24,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation